Development of Integrative Thematic Learning Models Based on Scientific Approaches and 21st Century Learning Skills - Muhammad, Muhammad; Pramono, Suwito Eko; Kustiono, Kustiono (Educational Management, 2021)
Referring to thematic learning that has not been optimized, this study aims to develop a quality and independent integrative thematic model, and to determine its effectiveness to improve learning outcomes and 21st century learning skills of elementary school students. This research was conducted using research and development designs (R&D) with preliminary study research stages, development stages, and evaluation stages. Model validation involves experts from academia and practitioners. The result of the effectiveness of the model is done through experimental activities using One Group Pretest-Posttest Design. The results of the model validation show that the integrative thematic learning component is valid with a percentage of 88.9% and 93%. The effectiveness of the product showed that an increase in learning outcomes can be seen in the average affective learning outcomes 89.1 and 85.4. The average psychomotor learning outcomes are 79.63 and 80.08. Then the results of the mastery test of the material (cognitive) after being treated with the results of 0.40 (medium category). Model effectiveness test showed an increase in learning outcomes after the use of thematic learning models based on scientific approaches with the value of Sig. (2-tailed) = 0,000. This shows that the model is effective in improving student learning outcomes and skills.